"Micro‐cultures" of conflict: Couple‐level perspectives on reasons for and causes of intimate partner violence in young adulthood. Issue 4 (21st June 2022) - Giordano, Peggy C.; Grace, Mackenzie M.; Longmore, Monica A.; Manning, Wendy D.
Abstract: Objective: To highlight the development of young adult couples' shared understandings about reasons for conflict in their relationships, views about why some disagreements included the use of aggression ("causes"), and gendered perspectives on these relationship dynamics. Background: Feminist theories have centered on relationship dynamics associated with intimate partner violence (IPV), but have focused primarily on men's concerns (e.g., jealousy) and use of violence as a means of control over female partners. The current analysis drew on symbolic interaction theory as a framework for exploring couple‐level concerns, and ways in which dyadic communication contributes to these understandings, or what can be considered "micro‐cultures" of conflict. Method: The study relied on in‐depth interviews with a heterogeneous sample of IPV‐experienced young adults who had participated in a larger longitudinal study (Toledo Adolescent Relationships Study [TARS]) and separate interviews with their partners ( n  = 90). Results: Analyses revealed that women's concerns about men's actions (e.g., infidelity) were frequently cited as reasons for serious conflicts, and showed significant concordance in partners' reports. Shared understandings sometimes extended to views on the role of more distal causes (e.g., family background) and the meaning(s) of each partner's use of aggression. Gendered dynamics included men's tendency to minimize women's concerns, and both partners' more open discussions of women's perpetration. Conclusions: Theories of IPV and associated programmatic efforts should include attention to the social construction of these "micro‐cultures, " as these shared meanings affect behavior, are potentially malleable, and add to the more intuitive focus on one‐sided forces of control and constraint.